The Effect of Arbuscular Mycorrhizal Fungi and Azotobacter on the Growth of Toona sureni Merr (Suren) Seedlings on Post-Coal Mining Land - Guswarni Anwar; Hasanudin Hasanudin; Hendri Bustamam (Journal of Tropical Mycorrhiza, 2022)
. This research aimed to investigate the growth of Toona sureni Merr (suren) seedlings inoculated with arbuscular mycorrhizal fungi (AMF) and azotobacter on land previously used for coal mining. We also investigated the source of AMF and azotobacter isolates, resulting in the best growth of suren seedlings on the post-coal mining land. We used a completely randomized design in a factorial manner with two treatment factors. The first factor was the inoculation of AMF isolates (C), which consisted of 5 levels, namely: without AMF (C0), AMF from the suren rhizosphere (C1), AMF from Gmelina arborea (gmelina) rhizosphere (C2), AMF from Durio zibethinus (durian) rhizosphere (C3), and AMF from Acacia mangium (acacia) rhizosphere (C4). The second factor was the inoculation of azotobacter isolates (A), which consisted of 4 levels, namely: without azotobacter (A0), azotobacter from the suren rhizosphere (A1), azotobacter from the gmelina rhizosphere (A3), and azotobacter from the durian rhizosphere (A4). Each treatment had six replications. Data analysis used ANOVA at a 5% test level. Then, we used the orthogonal contrast test to compare the growth of the inoculated seedlings with AMF and azotobacter with that of the un-inoculated seedlings. Meanwhile, to find out the source of isolates for AMF and azotobacter, which resulted in the best growth of the seedlings, we analyzed them with a two-way Duncan Multiple Range Test (DMRT). The results of the ANOVA showed that the AMF inoculation had a significant difference in height growth, diameter growth, and growth in the number of leaves. In contrast, azotobacter inoculation had no significant difference in the same growth variables. The interaction between AMF inoculation and Azotobacter was not significantly different in height growth but in diameter and leaf number growth. The DMRT analysis showed that AMF from suren rhizosphere isolates resulted in the best growth of the suren seedlings.